Field notes contributed by Dean Mosman, winter 1981-1982 - Mosman, Deanet al (1981)
Field notes were contributed by Dean Mosman. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1981-1982. Epson - sheet feed